A Critical Analysis of Humor in the Speech of Donald Trump - BOUSBIA LAICHE, Nousaiba; MESBAHI Kahina, Kahina (جامعة الوادي - University of Eloued, 2023)
The current study aims at analyzing selected samples from Donald Trump‟s humorous speeches delivered in various contexts. It mainly focuses on the strategic and pragmatic functions used in his utterances. To achieve this objective, Gaines‟s theory (2007) is adopted for the strategic functions analysis, as Searl‟s (1976) illocutionary acts theory for the pragmatic analysis. The identification of strategic functions shows that Trump used the dispositional, topical, and personal functions in his speech. The analysis of the findings revealed that he overused the topical function to introduce an issue. Besides, the identification of illocutionary acts indicates the presence of representative acts, directive acts, commissive acts, expressive acts, and declarative acts. The interpretation of the results unveiled the dominance of expressive acts, which reflect Trump‟s psychological state while addressing the audience. The research concludes that the study of both rhetorical and pragmatic functions has made it easy to comprehend the messages in former President Donald Trump‟s speech. It is recommended that additional studies should be conducted to examine the impact of humor on political discussion. Furthermore, it is important to take into account the public‟s perspective regarding Trump‟s use of insulting sarcasm.
Literature and Civilization
Keywords: Humorous Speech, Illocutionary Acts, Pragmatics, Speech Acts, Strategic Functions.